TINJAUAN YURIDIS IMPLIKASI MONOPOLI PERTAMINA DALAM KEBIJAKAN SATU PINTU TERHADAP INVESTASI SEKTOR HILIR MIGAS - Diva Jannatin Aliyah Arifin; Chesandra Auni Khairun Nisaa; Safira Andina Pratiwi; Nadiva Azzahra; Putri Daffa Rafidah (CV. Denasya Smart Publisher, 2025)
Base on law number 22 of 2021 concerning oil and gas serves as the main legal framework for Indonesia’s oil and gas governance by separating upstream and downstream activities. This regulation was designed to establish a more transparent, efficient, and competitive system to encourage private sector participation and strengthen national energy security. This study aims to examine the regulation of downstream oil and gas activities, analyze Pertamina’s authority in the management of oil and gas, and assess the impact of the single-gate fuel import policy on Indonesia’s investment climate. The research employs a normative legal method by reviewing legislation, Constitutional Court rulings, and relevant legal as well as economic literature on energy. The findings reveal that downstream activities are regulated under a clear legal basis through the upstream-downstream separation, with oversight carried out by BPH Migas, which holds the authority to set policies, conduct supervision, and regulate distribution. Pertamina, as a state-owned enterprise, has been granted a special mandate to distribute subsidized fuel, with extended authority until 2027. However, the single-gate fuel import policy creates a dilemma: while it strengthens state control over national energy supply, it simultaneously reduces competition and discourages foreign investment due to its monopolistic tendencies. The study concludes that the effectiveness of this policy depends on balancing state control with market openness. Therefore, transparent oversight mechanisms and harmonization with fair competition principles are essential to create a just and sustainable oil and gas investment climate in Indonesia. As a recommendation, the government should strike a balance between national energy control, market openness, and transparent oversight mechanisms to ensure that the management of oil and gas resources is carried out in accordance with the mandate of Article 33 of the 1945 Constitution, promoting justice and sustainability.